Effects of soil applied zinc and copper to young oil palms (Elaeis guineensis Jacqs.) - Mohd Su, Nurul Afiqah (2015)
Oil palm is an important commodity crop in Malaysia. Oil palm is suitable to be planted in Malaysia because of the good environmental factors. Soil is a medium for plant to grow and is a source of nutrients to the plants. Plant requires macro- and micronutrients for growth. Normally, macronutrient is required in larger amounts by the plant and only small amount of micronutrients needed. Nowadays oil palms grown in Malaysia is not being applied with micronutrient for growth but higher amounts of macronutrient.. Thus, this study was conducted to investigate the effects of zinc and copper used as soil application in young oil palm and also to investigate the differences in uptake between sulphate and EDTA source for Zinc and Copper. This experiment was conducted in Machap Estate, Melaka. The series for the soil is Bungor series. The experimental design used in this study was completely randomized design (CRD) with 7 treatments and 3 replication for each treatment. The treatments were CuSO4, CuEDTA, ZnSO4, ZnEDTA. N, P, K, Mg and B were applied to all the oil palm. The oil palm plants were sampled at 3 years after planting and 6 months after treatment were applied and analyzed for total nutrient contents including ZN and Cu. The soil properties such as soil pH, cation exchange capacity and exchangeable bases, organic carbon, available phosphorus, and available micronutrient were analyzed. The results of this study were non significant because there were factors that affect the data analysis. The target results of this study were the treated plants will have higher zinc and copper uptake and EDTA is a better source for Zinc and Copper than sulphate.